ChemInform Abstract: Synthesis and Binding Affinity of New 1, 4‐Disubstituted Triazoles as Potential Dopamine D3 Receptor Ligands. Issue 9 (4th March 2014) - Insua, Ignacio; Alvarado, Mario; Masaguer, Christian F.; Iglesias, Alba; Brea, Jose; Loza, Maria I.; Carro, Laura
Abstract A series of new 1, 4‐disubstituted triazoles (V) are synthesized using click chemistry methodology and evaluated as potential ligands on several subtypes of dopamine receptors.